2013
DOI: 10.1080/02755947.2013.829140
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models for Differentiating Habitat Use of Coastal Cutthroat Trout and Steelhead at the Reach and Landscape Scale

Abstract: Steelhead Oncorhynchus mykiss and Coastal Cutthroat Trout Oncorhynchus clarkii clarkii are closely related species that are difficult to differentiate as juveniles and are commonly sympatric at the watershed scale. If Cutthroat Trout spawning and early rearing occur in small streams, it is often difficult to assess which parts of a stream network are dominated by each species. In this study I used catch data from 649 sites in coastal British Columbia to develop quantitative models of species presence and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Interestingly, whereas sculpins, coastal cutthroat trout, and coho salmon were positively associated in terms of occurrence, all three of these species or groups were negatively associated with the presence of steelhead. Our findings are in agreement with Ptolemy [20], who reported that coastal cutthroat trout dominated in smaller streams whereas steelhead dominated in larger streams. Similarly, Rosenfeld et al [21] found coastal cutthroat trout and coho salmon densities to be highest in smaller streams.…”
Section: Co-occurrence Among Speciessupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, whereas sculpins, coastal cutthroat trout, and coho salmon were positively associated in terms of occurrence, all three of these species or groups were negatively associated with the presence of steelhead. Our findings are in agreement with Ptolemy [20], who reported that coastal cutthroat trout dominated in smaller streams whereas steelhead dominated in larger streams. Similarly, Rosenfeld et al [21] found coastal cutthroat trout and coho salmon densities to be highest in smaller streams.…”
Section: Co-occurrence Among Speciessupporting
confidence: 93%
“…These two species have more similar ecological characteristics (e.g., spring spawning, flexibility in expression of migratory life histories, and capacity to complete their life cycles in small streams), and can interact evolutionarily via hybridization, where there is potential for outbreeding depression [11]. Within the geographic extent we examined, it is possible that coastal cutthroat trout better adapted to live in low order streams [18], whereas steelhead (potentially due to their larger adult size [20]) are more likely to be present in larger streams: A pattern that is repeated within streams where only O. mykiss are present with resident individuals (usually referred to as rainbow trout) occupying headwaters and migratory forms (steelhead) in larger, downstream locations [8,23]. If some of the processes discussed here are in play, the complementary (allotropic) distribution of these two species can indirectly account for other species associations we detected (i.e., the consistent negative or positive association with coastal cutthroat trout and steelhead respectively).…”
Section: Co-occurrence Among Speciesmentioning
confidence: 99%
“…Migratory fish are affected in multiple locations and habitats by localized environmental, predation, and harvest factors. Despite repeat spawning and the ability to spawn at different ages, the Coastal Cutthroat Trout population in Irely Creek is confined to a small watershed-a common phenomenon for this subspecies (Ptolemy 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The fish likely out-migrate to the lake within 1-3 years of hatching, although some of the deeper, wood-rich pools may support a few adults year-round. Such restriction of Coastal Cutthroat Trout to small, cold headwater systems (stream order ≤ 3) is common (Sullivan et al 1987;Harvey 1998;Blakley et al 2000;Rosenfeld et al 2000;Boss and Richardson 2002;Berger and Gresswell 2009;Buehrens 2011;Buehrens et al 2013;Ptolemy 2013). Coastal Cutthroat Trout prefer mean annual flows (MAFs) of up to 0.63 m 3 /s and summer flows below 0.31 m 3 /s (especially 0.08-0.11 m 3 /s ;Trotter 1989;Ptolemy 2013), consistent with the estimated MAF of 0.40 m 3 /s for Irely Creek (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Slaney et al (1996) noted that the anadromous coastal cutthroat trout is the salmonid at greatest risk in British Columbia, and Johnson et al (1999) reported a lack of information on the species in Puget Sound and the probable low abundance in south‐western Puget Sound. As coastal cutthroat trout prefer small streams (Hartman & Gill, 1968; Rosenfeld et al, 2002; Buehrens et al, 2013; Ptolemy, 2013), which are more vulnerable to a range of disturbances, quantifying and protecting habitat is essential for managing their populations. In particular, defining the precise habitat preferences of coastal cutthroat trout for spawning and rearing is key to understanding how changing habitat conditions will affect populations (Rosenfeld, Porter, & Parkinson, 2000).…”
Section: Introductionmentioning
confidence: 99%